2017
DOI: 10.3390/ijms18051099
|View full text |Cite
|
Sign up to set email alerts
|

High-Mobility Group Box 1 Disrupts Metabolic Function with Cigarette Smoke Exposure in a Ceramide-Dependent Manner

Abstract: We have previously found that cigarette smoke disrupts metabolic function, in part, by increasing muscle ceramide accrual. To further our understanding of this, we sought to determine the role of the cytokine high-mobility group box 1 (HMGB1), which is increased with smoke exposure, in smoke-induced muscle metabolic perturbations. To test this theory, we determined HMGB1 from lungs of human smokers, as well as from lung cells from mice exposed to cigarette smoke. We also treated cells and mice directly with HM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…et al, 2017;Anroedh et al, 2018;Meeusen et al, 2018). In mice, HMGB1 injections were noted to increase ceramides in muscle cells, especially C16 and C24 ceramides, enhance reactive oxygen species (ROS) production, and disrupt mitochondrial and insulin function, effects were alleviated with ceramide inhibition (Taylor et al, 2017). The present study also demonstrated that HMGB1 and NOE similarly increased long-chain ceramides including C14, C16, C18, C20, C22, and C24 ceramides.…”
Section: Discussionsupporting
confidence: 65%
“…et al, 2017;Anroedh et al, 2018;Meeusen et al, 2018). In mice, HMGB1 injections were noted to increase ceramides in muscle cells, especially C16 and C24 ceramides, enhance reactive oxygen species (ROS) production, and disrupt mitochondrial and insulin function, effects were alleviated with ceramide inhibition (Taylor et al, 2017). The present study also demonstrated that HMGB1 and NOE similarly increased long-chain ceramides including C14, C16, C18, C20, C22, and C24 ceramides.…”
Section: Discussionsupporting
confidence: 65%
“…Two potential hypotheses for this reduced proliferation are (a) an overall reduction in cellular metabolism due to C2 treatment impacting mitochondrial function, and (b) ciliary disruption due to C2 treatment disrupts cellular functionality and division. Ceramides are implicated in reducing the mitochondrial respiration of skeletal muscle cells, 71,72 and several lines of study have indicated a potential role of primary cilium in the development of NTDs. [73][74][75][76] Ceramides are reported to regulate the generation and elongation of primary cilium.…”
Section: Embryonic Defect Datamentioning
confidence: 99%
“…One of the earliest observations of this interaction was the production of inflammatory cytokines from adipose, a prototypical metabolic tissue, which resulted in defects in systemic sensitivity to insulin, a prototypical metabolic hormone [1]. Macrophages, whether adipose or otherwise, are highly relevant to this process, with a prominent line of evidence suggesting that macrophage activation provides an inflammatory ā€œsparkā€ that ignites systemic downstream cardiometabolic complications [2,3,4]. Insofar as the lung, being one of two sites of direct environmentā€“host interaction, is enriched with macrophages, evidence implicating the macrophage and its inflammatory actions in metabolic disruption in response to inhaled noxious stimuli is strong [5].…”
Section: Introductionmentioning
confidence: 99%
“…Unsurprisingly, consistent DEP inhalation is implicated with several cardiorespiratory disorders and mortality [7], with both epidemiological [8] and molecular [7] evidence indicating a primary role of the lung macrophage. At least some of the pathology associated with noxious stimuli exposure is a result of macrophage-induced cytokine release, which has been a focus of earlier work from our lab [4,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation